GERAK SENDI PEMBELAJARAN PAKEM UNTUK MENINGKATKAN DAYA INGAT SISWA PADA PEMBELAJARAN SENDI MANUSIA - AMIRUDDIN AMIRUDDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
The purpose of this best practice is to find out how the implementation of the PAKEM approach to joint motion in improving the learning memory of class VIII A students of SMP Negeri 1 Anggaberi, Konawe Regency in the discussion of the types of human joints in the subject of Natural Sciences. The results of the learning activities indicate that the application of the Pakem learning approach with joint motion can improve the ability to remember the subject matter of the types of human joints in class VIII A students of SMP Negeri 1 Anggaberi. The results of the quiz on identifying the types of joints in humans before the application of the joint movement grip learning in previous learning activities showed the average percentage of ability to remember materials to identify materials only reached a value of 50%, still below the KKM value set for the types of joints in humans, and increased after learning activities that apply the gripping joint motion approach to the quiz results considering the material on identifying joints in humans, the percentage of analysis of quiz results reaches a value of 85%, above the KKM that has been set on the material for joint types in humans. ABSTRAKTujuan best practice ini adalah untuk mengetahui bagaimana implementasi pendekatan PAKEM gerak sendi dalam meningkatkan daya ingat belajar siswa kelas VIII A SMP Negeri 1 Anggaberi Kabupaten Konawe pada pembahasan materi jenis-jenis sendi manusia, mata pelajaran Ilmu Pengetahuan Alam. Hasil kegiatan pembelajaran menunjukkan bahwa penerapan pendekatan belajar Pakem dengan gerak sendi dapat meningkatkan kemampuan mengingat materi pelajaran jenis-jenis sendi manusia pada siswa kelas VIII A SMP Negeri 1 Anggaberi. Hasil kuis mengidentifikasi jenis sendi pada manusia sebelum penerapan pembelajaran Pakem gerak sendi pada kegiatan pembelajaran sebelumnya menunjukkan rata-rata persantase kemampuan mengingat materi mengidentifikasi materi hanya mencapai nilai 50%, masih di bawah nilai KKM yang ditetapakan pada jenis sendi pada manusia, dan mengalami peningkatan setelah kegiatan pembelajaran yang menerapkan pendekatan Pakem gerak sendi hasil kuis mengingat materi mengidentifikasi sendi pada manusia persentase analisis hasil kuis mencapai nilai 85%, di atas KKM yang telah ditetapkan pada materi jenis sendi pada manusia.